Analisis Struktur Portal Bidang Dengan Beban Lateral Menggunakan Metode Elemen Hingga - Pasaribu, Humisar; -, Bartholomeus (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2023)
It is necessary to carry out a safety and comfort inspection of the existing wharf structure to ensure the facility’s service life. To check the safety and comfort, it is necessary to do a structural analysis. In the world of civil engineering, there are many problems in analyzing structures that need to be analyzed for working loads or assessing the existing wharf structures that are loaded by ship berthing loads and loads on the floor plates. This research is limited by conducting research on port ports that are burdened with berthing loads. The results of this study are deformation at the nodes in the horizontal and vertical directions of the global and local axes. Based on the analysis carried out, a maximum horizontal deformation of 4.363 cm is obtained and is less than 0.5% H (or 7.4 cm) as required in SNI 8460:2017. Thus, it can be concluded that the structure can still bear the impact of a ship weighing 30,000 DWT.